Prototype sistem pakar untuk penjadwalan - Catur Edi Widodo (Youngster Physics Journal, 2017)
Scheduling is a complex problem, which requires huge resource to solve. The resources required include faculty, lecturer, classrooms, and the period of time for teaching. The solution of academic scheduling in large scale still face up so many obstacles to done manually. The college has to give a schedule in certain time when every academic activity is not crash. Scheduling is needed to anticipate crash of students hours to study and lectures time to teach. Scheduling have to fill the boundary and condition so that it convenient when it used. Under these conditions, a system is needed to set the schedule will not crash so as to improve the work of everyone. The possibility to find the best result and the implemented method approach to solve the problem is use constrain satisfaction method. Making this scheduling application is started with build table of combination from class data, room data, lecture data and time slot and followed by initiation and calculation with genetic algorithm. During the process, we generate the time and room data of each lecturer and test if crash or no crash. From the result, indicate fine schedule means there is no crash between each other and all class can be scheduled. Scheduling is optimal if all of space and time that is provided can be filled without happen crash.Keywords: scheduling, generate and test, constraint satisfaction, crash.